Wizards of Once, The : Twice magic - Cowell, Cressida (New York ; Boston : Little, Brown and Company, 2019)
"The Wizard boy Xar and the Warrior girl Wish must learn to work together in order to find the ingredients for an ancient Witch-killing spell if they are to save the wildwoods"--
"From the author of How to Train Your Dragon"--Dust jacket.
"Originally published in 2018 by Hodder Children's Books in Great Britain."
Keywords: Adventure and adventurers -- Fiction; Princes -- Fiction; Princesses -- Fiction; Wizards -- Fiction; Witches -- Fiction; Magic -- Fiction